Spectroscopic follow-up of a cluster candidate at z = 1.45 - Breukelen, C; Cotter, G; Rawlings, S; Readhead, T; Bonfield, D; Clewley, L; Ivison, R; Jarvis, M; Simpson, C; Watson, M (2007)
We have obtained deep optical spectroscopic data of the highest-redshift cluster candidate (z ~ 1.4, CVB13) selected by Van Breukelen et al. (2006) in a photometric optical/infrared catalogue of the Subaru XMM-Newton Deep Field. The data, which comprise 104 targeted galaxies, were taken with the DEep Imaging Multi-Object Spectrograph (DEIMOS) on the Keck 2 telescope and yielded 31 secure redshifts in the range 1.25 < z < 1.54 within a 7' x 4' field centred on CVB13. Instead of one massive cluster at z = 1.4, we find evidence for three projected structures at z = 1.40, z = 1.45, and z = 1.48. The most statistically robust of these structures, at z = 1.454, has six spectroscopically confirmed galaxies. Its total mass is estimated at > 10^14 M_sun and it may therefore be termed a cluster. There is an X-ray source at the cluster position which is marginally spatially resolved but whose X-ray spectrum is too hard to be thermal cluster emission. Its origin could be the summed X-ray emission from active galaxies in, and projected onto, the cluster. Serendipitously we have discovered a cluster at z = 1.28 with a mass of > 10^14 M_sun at the same position on the sky, comprising six spectroscopically confirmed cluster galaxies and at least one additional radio source. The selection of CVB13 for the cluster catalogue was evidently aided by the superposition of other, presumably lower-mass, structures, whereas the single cluster at z = 1.28 contained too few galaxies to be isolated by the same algorithm. Given the complicated nature of such structures, caution must be employed when measuring the mass function of putative high-redshift clusters with photometric techniques alone.